The Relationship Between Learning Interest, Intrinsic Motivation, and Practical Learning Outcomes of Network System Administration in Vocational High Schools - Yosafatur Aprendy Panjaitan; Dian Permata Sari (Journal of Educational Sciences, 2026)
The rapid development of digital technology requires vocational high schools to produce highly competitive graduates. In the Computer and Network Engineering program, Network System Administration (ASJ) is a core subject requiring technical and problem-solving skills through practical learning. Therefore, this study aims to examine the relationship between learning interest and intrinsic motivation with conceptual practice-based learning outcomes in the ASJ subject. A quantitative correlational approach was employed. The sample consisted of 66 eleventh-grade vocational students, selected through purposive sampling. Data were collected using validated questionnaires and case study-based tests, then analyzed using the Spearman rank correlation due to the non-normal distribution of the data. The findings revealed a weak but significant positive relationship between learning interest and practical learning outcomes (ρ = 0.244, p = 0.048). Conversely, intrinsic motivation showed no significant relationship with learning outcomes (ρ = 0.171, p = 0.170). In conclusion, while learning interest positively contributes to students' conceptual understanding of network practices, it is not the dominant factor. The results imply that practical learning success in vocational education is also heavily influenced by cognitive abilities, instructional strategies, and learning facilities rather than solely by internal affective factors.